The Lure of Live Coding; The Attraction of Small Data. - Guzdial, Mark; Barr, Valerie (Communications of the ACM, 2013)
The article relates the author's experience while attending a seminar on live coding, which is a performance involving computer programmers who create improvised music in front of an audience. Highlights of the seminar entitled "Collaboration and Learning Through Live Coding," organized by live coding experts Alan Blackwell, Julian Rohrhuber and Alex McLean, are presented. Several websites related to live coding are presented. The session on about the impact of live coding on software engineering led by Robert Biddle is mentioned.